The Effect Analysis of Asset Management and Company Size On Financial Performance Using the Multiple Linear Regression Analysis Method: Analisis Pengaruh Manajemen Aset dan Ukuran Perusahaan Terhadap Kinerja Keuangan Menggunakan Metode Analisis Regresi Linear Berganda - Sofia Fitri Anasari; Rr. Rochmoeljati (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
PT XYZ is a company engaged in the marine industry sector and plays an important role in shipbuilding. Management of company assets is a key factor in ensuring smooth operations and achieving the company's financial performance. However, asset management is faced with various challenges, such as high asset maintenance costs, depreciation, and the need to continuously update and improve asset quality to remain competitive. This study aims to evaluate the impact of asset management and company size on the company's financial performance. The study was conducted using multiple linear regression analysis methods processed through SPSS software. The data analyzed came from the company's financial reports and operational information for 12 months in 2023. The study findings show that asset management has a significant positive effect on the company's financial performance, while size only has a small effect. The linear regression equation obtained is Y = -291.213 + 165.600X1 + 12.698X2. Looking at this equation, it can be concluded that financial performance will increase by 165.600 for each increase in the asset management variable, and financial performance will increase by 12.698 for each increase in the company size variable. This study can be used by company management as a reference to improve financial performance by optimizing asset management and formulating more effective company growth strategies.